Investigating the effect of pre-treatment on the drying kinetics and quality traits of rice noodles - Ismail, Muhammad Heikal (2019)
Rice noodle has long been a very common food to most East Asians. Moreover, the overwhelming trend towards gluten-free food which introduces positive health beneficial effects has currently promoted rice noodle throughout the world. In spite of that, fresh rice noodle is truly perishable and prone to degradation within several days. Therefore, there is an urgent need to produce the good preservation of high quality fresh rice noodle of a good textural and cooking quality with an adequate shelf life. Therefore, the shelf life of rice noodle will be prolonged by the means of drying. Unfortunately, there is a lack of research on the processing aspects to produce better quality of dried rice noodle.